Foundations of Education - AbuAssaly-George, Lisa; Bunney, Kanoe; De Valdenebro, Ceci; Mead, Tanya (Open textbook library., 2023)
This dynamic and equity-focused Open Educational Resource serves as a multifaceted textbook for Foundations of Education courses in post secondary institutions.